IMPLEMENTATION OF COLLABORATIVE TEACHER BASED MORAL DEVELOPMENT METHODS AT SMPN 16 SOUTH JAKARTA - Mochamad Daffa Akmal (STKIP Subang, 2025)
This study examines the collaborative methods of moral development implemented by Islamic Education teachers (PAI), Guidance and Counseling teachers (BK), subject teachers, and homeroom teachers in addressing students’ negative behavior at SMPN 16 South Jakarta. Moral issues among adolescents such as bullying, truancy, smoking, disrespect toward teachers, verbal aggression, and vandalism require an integrated and systematic approach. Using a qualitative descriptive method with a case study design, data were collected through interviews, observations, and document analysis. The participants included PAI teachers, BK teachers, subject teachers, homeroom teachers, and selected students. The findings show that the collaborative moral development in the school is carried out through various methods, including role modeling, habituation, advice, storytelling, motivation, peer influence, cause and effect explanation, discipline, and educative punishment. These methods are applied through coordinated communication and shared responsibility among teachers. Collaboration enhances consistency in moral guidance and enables teachers to more effectively identify students’ behavioral problems while ensuring appropriate follow-up actions.This study concludes that collaborative methods significantly strengthen the effectiveness of moral development, foster positive student behavior, and support the creation of a holistic character education environment in schools.